(3gOGjI GdQGei Edi WQjb GdeQGeis - (3CMeO Hf EHQGgje Hf CMeO SHW GHf MQR Gddg, CHh GdYHGSs
(3ChdgG (B:s
(3Ce HYO ajG SYO GYde Cfi CNh Md hTO , hbO GSJNQJ Gddg JYGdi Cf CgPH cJGHkG HeG Ydjg Cgd gPG Gdaf hbhGYOg hMdGdg h MQGeg s
(3ai Yde GdQei HGdHfObs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs